Local stability analysis and numerical simulation of a mathematical model for rabies transmission - Castro, Franchine Faith M. (College of Science, University of the Philippines Cebu, 2022)
In this paper, we analyze K. Addo's epidemiological model [1] for rabies transmission in a dog population. The model considers an SEIR population and is described by a system of autonomous nonlinear equations. We prove the boundedness and positivity of solutions of the system. We show and investigate the existence and stability of the equilibrium points of the system through the basic reproduction number which is computed using the next generation matrix. In addition, numerical examples were utilize using MATLAB to facilitate the analytical findings and provide biological interpretations. The results show that changes in the rate of rabies vaccination among dogs had a considerable impact on the rate of rabies transmission. This has been demonstrated that increasing the vaccination rate but decreasing the transmission rate among dogs will not cause an epidemic, however increasing the transmission rate while reducing the vaccination rate in dogs will trigger an outbreak.